The PAR complex controls the spatiotemporal dynamics of F-actin and the MTOC in directionally migrating leukocytes - Crespo, Carolina Lage; Wittbrodt, Joachim (2014)
Inflammatory cells acquire a polarized phenotype to migrate towards sites of infection or injury. A conserved polarity complex comprising PAR-3, PAR-6 and atypical protein kinase C (aPKC) relays extracellular polarizing cues to control cytoskeletal and signaling networks affecting morphological and functional polarization. However, there is no evidence that myeloid cells use PAR signaling to migrate vectorially in three-dimensional (3D) environments in vivo . Using genetically encoded bioprobes and high-resolution live imaging, we reveal the existence of F-actin oscillations in the trailing edge and constant repositioning of the microtubule organizing center (MTOC) to direct leukocyte migration in wounded medaka fish larvae ( Oryzias latipes ). Genetic manipulation in live myeloid cells demonstrates that the catalytic activity of aPKC and the regulated interaction with PAR-3 and PAR-6 are required for consistent F-actin oscillations, MTOC perinuclear mobility, aPKC repositioning and wound-directed migration upstream of Rho kinase (also known as ROCK or ROK) activation. We propose that the PAR complex coordinately controls cytoskeletal changes affecting both the generation of traction force and the directionality of leukocyte migration to sites of injury.